2017
DOI: 10.1021/acs.inorgchem.7b00458
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Negative Thermal Expansion Perovskite LaCu3Fe4O12: Pressure-Triggered Transition of Magnetism, Charge, and Spin State

Abstract: The A-site ordered negative thermal expansion material LaCuFeO (LaCFO) was comprehensively investigated by using first-principles calculations. A pressure-triggered crystal structural phase transition from space group Im3̅ (No. 204) to Pn3̅ (No. 201) and magnetic transformation from a G-type antiferromagnetic (G_AFM) ground state to ferrimagnetic (FerriM) coupling were observed in LaCFO via gradual compression of the equilibrium volume. Correspondingly, the Fe-Cu intersite charge transfer from Fe to Cu 3d orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The most frequently reported ones are phase transitions (ice/water), electronic valence transitions [19][20][21], ferroelectric ordering [22][23][24], contraction of zeolites (siliceous or ZrW 2 O 8 ) by changing in bridging M-O-M bond angles [25][26][27] or orbital and magnetic ordering [28]. While there have been some reports of perovskite materials with NTE during the last three decades [29][30][31][32][33], such observations are unusual as perovskites in the form ABO 3 generally do not exhibit NTE properties [30]. Another factor that is important for thermal expansion characteristics, particularly for perovskite systems in SOC operation, is the changes to the composition.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported ones are phase transitions (ice/water), electronic valence transitions [19][20][21], ferroelectric ordering [22][23][24], contraction of zeolites (siliceous or ZrW 2 O 8 ) by changing in bridging M-O-M bond angles [25][26][27] or orbital and magnetic ordering [28]. While there have been some reports of perovskite materials with NTE during the last three decades [29][30][31][32][33], such observations are unusual as perovskites in the form ABO 3 generally do not exhibit NTE properties [30]. Another factor that is important for thermal expansion characteristics, particularly for perovskite systems in SOC operation, is the changes to the composition.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, de Groot et al reported the first half metal . Since then, a wide variety of half-metallic magnets with different crystal structures were proposed in both experiment and theory. However, it is still a big challenge to search for high-performance half metals with potential application near room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, first-principles calculations based on the DFT method were performed as implemented in the Vienna Ab initio Simulation Package (VASP) within the projector-augmented plane wave (PAW) method and WIEN2k code based on the full potential linearized augmented-plane-wave (FL-LAPW) method. We performed structural optimization in the former code and calculated electronic as well as magnetic characteristics in the latter one, which was proved to be a conventional and effective way to deal with the systems involving f-electrons and/or magnetic characteristics. In both packages, we employed the exchange–correlation functional given by generalized gradient approximation (GGA) in the form of Perdew, Burke and Ernzerhof revised for solids (PBEsol) . Hubbard U correction was applied to Eu 4f states and Mn 3d states .…”
Section: Computational Detailsmentioning
confidence: 99%